B cell synovitis and clinical phenotypes in rheumatoid arthritis: relationship to disease stages and drug exposure - Humby, F; Bugatti, S; Fossati-Jimack, L; Rizvi, H; Lucchesi, D; Lliso-Ribera, G; Nerviani, A; Hands, RE; Giorli, G; Frias, B; Thorborn, G; Jaworska, E; et al. (Wiley, 2019)
Objective: To define the relationship of synovial B cells to clinical phenotypes at different stages of disease evolution and drug exposure in rheumatoid arthritis (RA). Methods: Synovial biopsy specimens and demographic and clinical data were collected from 2 RA cohorts (n = 329), one of patients with untreated early RA (n = 165) and one of patients with established RA with an inadequate response to tumor necrosis factor inhibitors (TNFi‐IR; n = 164). Synovial tissue was subjected to hematoxylin and eosin and immunohistochemical staining and semiquantitative assessment for the degree of synovitis (on a scale of 0–9) and of CD20+ B cell infiltrate (on a scale of 0–4). B cell scores were validated by digital image analysis and B cell lineage–specific transcript analysis (RNA‐Seq) in the early RA (n = 91) and TNFi‐IR (n = 127) cohorts. Semiquantitative CD20 scores were used to classify patients as B cell rich (≥2) or B cell poor (<2). Results: Semiquantitative B cell scores correlated with digital image analysis quantitative measurements and B cell lineage–specific transcripts. B cell–rich synovitis was present in 35% of patients in the early RA cohort and 47.7% of patients in the TNFi‐IR cohort (P = 0.025). B cell–rich patients showed higher levels of disease activity and seropositivity for rheumatoid factor and anti–citrullinated protein antibody in early RA but not in established RA, while significantly higher histologic synovitis scores in B cell–rich patients were demonstrated in both cohorts. Conclusion: We describe a robust semiquantitative histologic B cell score that closely replicates the quantification of B cells by digital or molecular analyses. Our findings indicate an ongoing B cell–rich synovitis, which does not seem to be captured by standard clinimetric assessment, in a larger proportion of patients with established RA than early RA.